The Darkest Phase for Family: Child Marriage Prevention and Its Complexity in Indonesia - Latifiani, Dian (Universitas Negeri Semarang, 2019)
The research is intended to examine how child marriage happened and the implementation of policy to prevent the child marriage. The research also examine some cases concerning to child marriage and its complex condition, especially in some area of Central Java, Indonesia. The method used to obtain the main data for the research is by interviewing and observing the main site location, at Munding Vilage Semarang Regency. Some related government offices also become one of the sources of data. The research emphasized that child marriage occurs because of the education of the bridegroom's children, the local culture of marriage at the age of the child is better than marriage in high school, economic factors of the child's family and social or environmental factors of the child. Impact of child marriages (women): vulnerable to divorce, psychological problems that are not yet stable in the management of the household, the breakup of formal education, reproductive health is not ready. The research highlighted that local culture is a challenge in opposing marriage at the age of the child. The research concluded that preventive efforts carried out by related institutions through education complaints in accordance with the main tasks of each related institution.